The causal relationship between immune cells and knee osteoarthritis: Mendelian randomization study - Chenghao Gao; Hongxu Pu; Yifan Zeng; Jun Xiao (BMC Musculoskeletal Disorders)
Abstract Knee osteoarthritis (OA) is a common degenerative joint disease that affects millions of people worldwide. Inflammation is one of the key pathogenic factors of knee OA. However, the causal relationship between immune cells and knee OA development remains unclear. Herein, we used Mendelian randomization (MR) analysis to evaluate causal relationship between 731 immune cells and knee OA. Several methods were applied to ensure the robustness of our results, including inverse-variance weighted (IVW), simple mode, weighted median, weighted mode, and MR-Egger. We found that 23 immune cell phenotypes were causally associated with knee OA (P < 0.05), including various subpopulations of B cells, T cells, TBNK (T cells, B cells, Natural Killer cells) and monocytes, which was confirmed by heterogeneity, sensitivity, and pleiotropy tests. B cells had dominant effects on OA development, and specifically, our findings suggest that BAFF-R in IgD + CD38- unswitched memory B cells may have a protective role, whereas CD25 in IgD + CD24 + B cells appears to be associated with increased risk, pending further validation. Moreover, a higher population of regulatory T (Treg) cells indicated a higher risk of OA and reversely, OA could induce Treg differentiation. Collectively, our study identified several immune cells that were closely related to OA development, which provided novel insights into the pathogenesis of OA and therapeutic targets for OA treatment.